Eles partiram cedo : morte, luto e resiliência diante da fé cristã - Pasa, Fabiane Maria Lorandi (2013)
The guiding aspect of this paper starts from the dialogue between Theology and Psychology on the semantics of death, the psychological processes emerging from mourning mainly in the violent loss of a child and how the faith in the Resurrection can assist in becoming resilient in this time of grief and loss. The survey places emphasis on the concept of death and resurrection in Theology, taking, as its starting point, the death of Christ and its meaning for the Christian, the human finitude, and Christian hope in the resurrection and eternal life. The study is based on the reflection of theologians and psychologists addressing the topic in question. A field survey with twenty mothers in mourning was held, the analysis of which shows significant aspects for an interdisciplinary activity, demonstrating the relevance of the theme in offering contribution for Theology in its pastoral action, and as science, which seeks to understand the mystery of human life in all its dimensions and stages: from beginning to end of life.